Integrating Local Culture to Work Ethics: A Holistic Approach to Mitigating Problematic Financing in Islamic Banks - Budiono, I Nyoman; Abu Bakar, Ahmad; Haddade, Hasyim; Daily, Syarmillah; Husain, Hartina (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2024)
Purpose – This study aims to explore the integration of Siri' culture, Islamic work ethic, and the 5C principles in preventing problematic financing in Islamic banks, particularly within the Bugis-Makassar community. Method – Using a qualitative approach, the research employed interviews, document analysis, and field observations to gather data. Thematic analysis was conducted to identify patterns and insights related to the interplay of cultural, ethical, and technical frameworks in financing practices. Findings –. The results reveal that Siri' culture fosters high moral responsibility among customers, enhancing their commitment to fulfilling financial obligations. Islamic work ethic strengthens accountability and transparency among bank employees, while the 5C principles provide a structured framework for financing decisions.. Practical implications – Banks can incorporate cultural dimensions, such as Siri' values of honesty (ada' tongeng), respect (sipakatau), and adherence to principles (getteng), into their credit analysis frameworks. This approach can enhance the quality of financing decisions by integrating ethical and moral considerations with technical assessments.. Originality/value – holistic approach, integrating cultural, ethical, and technical dimensions to mitigate financing risks